An acoustic field-based conformal transfection system for improving the gene delivery efficiency. (6th May 2021) - Xie, Liting; Wang, Jieqiong; Zhao, Shuai; Lai, Man Lin; Jiang, Tianan; Yan, Fei
Abstract : An acoustic field-based conformal transfection system for improving the gene delivery efficiency, which provides an effective ultrasound-based gene delivery approach, especially for suspension-cultured cells. Abstract : Ultrasound-activated microbubble destruction is a promising platform for gene delivery due to the low toxicity, non-invasiveness, and high specificity. However, the gene transfection efficiency is still low, especially for suspension cells. It is desirable to develop a universal gene delivery tool that overcomes the drawbacks existing in ultrasound-mediated methods. Here, we present a three-dimensional acoustic field-based conformal transfection (AFCT) system by designing a Sono-hole that can fit the three-dimensional acoustic field to maximally utilize the acoustic energy from bubble cavitation, thus greatly promoting the gene delivery efficiency. Surprisingly, compared with the traditional two-dimensional transfection system, the gene transfection efficiency of the AFCT system increased by more than 3 times, achieving nearly 30%. The parameters including acoustic pressure, duration, duty cycle, DNA concentrations, and bubble kinds were optimized to obtain higher gene transfection. In conclusion, our study provides an effective ultrasound-based gene delivery approach for gene transfection, especially for suspension-cultured cells.